2019
DOI: 10.18203/2320-6012.ijrms20192933
|View full text |Cite
|
Sign up to set email alerts
|

Malignant nodular hidradenoma-inguinal region clinically masquerading as squamous cell carcinoma: a case report

Abstract: Malignant Nodular hidradenoma is an extremely rare aggressive tumour originating from eccrine sweat glands with an incidence of <.001%. So far less than 80 cases have been reported in the literature. It’s known for its local recurrence (50%) and metastasis (60%) and hence early diagnosis and radical treatment is mandatory. But differentiating it from its benign counterparts and other skin tumour mimics is challenging, due to its histopathological similarity & lack of diagnostic immunomarkers. Authors re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…It has been estimated that 6-7% of benign neoplasms will mysteriously convert into malignant tumors [ 9 ]. Contrary to an Indian study that reported men between the ages of 50 and 70 were somewhat more likely to develop hidradenocarcinoma, our female patient, aged 55, developed the disease as a primary instance [ 8 ].…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…It has been estimated that 6-7% of benign neoplasms will mysteriously convert into malignant tumors [ 9 ]. Contrary to an Indian study that reported men between the ages of 50 and 70 were somewhat more likely to develop hidradenocarcinoma, our female patient, aged 55, developed the disease as a primary instance [ 8 ].…”
Section: Discussioncontrasting
confidence: 69%
“…The majority of individuals with this type of swelling have an asymptomatic clinical course throughout their disease history, with pain and bleeding upon contact as the most prevalent symptoms. These tumors often have a diameter of 1-5 cm [ 8 ]. However, due to the patient’s delayed presentation to the clinical setting, a bigger mass measuring 7-9 cm with overt ulceration was observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hidradenocarcinoma has an incidence of less than 0.001% (15,16). Because it is so rare, the treatment protocols used are a subject of debate.…”
Section: Discussionmentioning
confidence: 99%